The Methodology of economics: Or how economists explain - Blaug M. (Mark) (Cambridge: Cambridge University Press, 1994)
This is a revised and updated edition of the classic work on the methodology of economics, in which Professor Blaug develops his discussion of the latest developments in macroeconomics, general equilibrium theory, and international trade theory.
(NP(B/11245s
Keywords: methodology -- history -- economics